2023
DOI: 10.3389/fimmu.2023.1083333
|View full text |Cite
|
Sign up to set email alerts
|

A novel oral formulation of the melanocortin-1 receptor agonist PL8177 resolves inflammation in preclinical studies of inflammatory bowel disease and is gut restricted in rats, dogs, and humans

Abstract: IntroductionPL8177 is a potent and selective agonist of the melanocortin 1 receptor (MC1R). PL8177 has shown efficacy in reversing intestinal inflammation in a cannulated rat ulcerative colitis model. To facilitate oral delivery, a novel, polymer-encapsulated formulation of PL8177 was developed. This formulation was tested in 2 rat ulcerative colitis models and evaluated for distribution, in vivo, in rats, dogs, and humans. MethodsThe rat models of colitis were induced by treatment with 2,4-dinitrobenzenesulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…More recently, the anti-inflammatory action of PL-8177 was also confirmed in another model of DNBS-and DSS-induced colitis in mice [73]. Specifically, however, the authors also evaluated the pharmacokinetics of PL-8177 after a single oral administration of 70 µg by marking it with 14 C in dogs, showing a higher concentration in the colic than in the upper gastrointestinal tract.…”
Section: Mc1r Mediates and Improves Intestinal Inflammation In Major ...mentioning
confidence: 98%
“…More recently, the anti-inflammatory action of PL-8177 was also confirmed in another model of DNBS-and DSS-induced colitis in mice [73]. Specifically, however, the authors also evaluated the pharmacokinetics of PL-8177 after a single oral administration of 70 µg by marking it with 14 C in dogs, showing a higher concentration in the colic than in the upper gastrointestinal tract.…”
Section: Mc1r Mediates and Improves Intestinal Inflammation In Major ...mentioning
confidence: 98%
“…A special application of microdosing was employed by Palatin Technologies to assess the distribution of PL8177, a potent and selective melanocortin-1 (MC-1) receptor agonist developed as a gastrointestinal anti-inflammatory agent in inflammatory bowel disease (IBD), after the oral administration of a microdose of [ 14 C]-PL8177 as an Eudragit ® polymer-encapsulated formulation in humans ( Dodd et al, 2023 ). Polymer encapsulation was designed to protect PL8177 from degradation in the upper gastrointestinal (GI) tract and allow its release in the lower GI tract, where it would be expected to exert its effect.…”
Section: Applications Of Phase 0/microdose Studies and Related Designsmentioning
confidence: 99%
“…Recent studies have found that MC1R not only has a regulatory role in melanoma but also in uences the prognosis of other tumors, such as breast cancer [22], skin cancer [23] and prostate cancer [24]. In addition, MC1R has also been identi ed as a biomarker associated with some colon diseases, such as colitis [25] and colorectal cancer [26]. However, the exact mechanism by which MC1R affects colon cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%